Long-term survival with extended lateral lymphadenectomy for lateral lymph node recurrence after laparoscopic abdominoperineal resection for rectal adenosquamous carcinoma: a case report - Takahiro Yokose; Seiichiro Yamamoto; Takeshi Nagase; Toshio Kanai; Kiminori Takano; Taku Fujii; Mai Tsutsui; Motohito Nakagawa; Hiroki Ochiai; Kaori Kameyama (Surgical Case Reports)
Abstract The patient was a 54-year-old female who presented with the chief complaint of melena. Lower gastrointestinal endoscopy detected a type 1 tumor extending from the anal canal to the rectum. CT did not detect any distant metastasis. Proximal D3 lymphadenectomy with laparoscopic abdominoperineal resection was performed for stage IA rectal cancer. In the histopathological examination, the tumor was identified as stage IIIa adenosquamous carcinoma. Although the patient underwent postoperative adjuvant chemotherapy with S-1, a recurrent left lateral lymph node tumor was detected on CT and PET 12 months later. The patient underwent the treatment with mFOLFOX + bevacizumab for 6 months. However, the tumor continued to progress, and therefore, extended lateral lymphadenectomy was performed 21 months after the first surgery. The patient did not undergo postoperative adjuvant therapy and is alive without recurrence 90 months after the first surgery and 70 months after the reoperation. Adenosquamous carcinoma of the rectum is a rare histological type of colorectal cancer for which there is no effective treatment besides surgical resection, and its prognosis is known to be worse than that of adenocarcinoma. Since there has been no report of long-term survival after extended lateral lymphadenectomy for recurrent lateral lymph node tumors following surgery for adenosquamous carcinoma of the rectum, herein, we report the case with a review of the literature.